Systemic therapy and prognosis of older patients with stage II/III breast cancer: A large-scale analysis of the Japanese Breast Cancer Registry. (September 2021) - Yamada, Akimitsu; Kumamaru, Hiraku; Shimizu, Chikako; Taira, Naruto; Nakayama, Kanako; Miyashita, Mika; Honma, Naoko; Miyata, Hiroaki; Endo, Itaru; Saji, Shigehira; Sawaki, Masataka
Abstract: Aim: This study aimed at investigating the real-world prognostic impact of systemic treatment in older patients with stage II/III breast cancer (BC). Methods: This retrospective cohort study included patients with stage II/III primary BC, aged ≥55 years, and registered in the Japanese Breast Cancer Registry from 2004 to 2011. The clinicopathological characteristics, treatments, and prognosis of patients aged ≥75 years (older) were compared to those of younger patients. Results: In total, 56, 093 patients (12, 727, ≥75 years; 17, 860, 65–74 years; 25, 506, 55–64 years) were enrolled. In the older group, 9.2% with a luminal (hormone receptor [HR]+/human epidermal growth factor receptor 2 [HER2]-), 32.9% with a triple-negative (TN, HR-/HER2-), and 27.4% with a HER2-positive (any-HR/HER2+) receptor were administered chemotherapy. In those with luminal cancer, the 5-year breast cancer-specific survival (BCSS) was approximately 95% in all age groups. Meanwhile, among those with TN and HER2-positive BC, the older group had a poorer BCSS. The 5-year overall survival (OS) was also poorer in the older group across all subtypes. Among older patients matched using clinicopathological factors, chemotherapy use was associated with improved OS in the luminal and HER2-positive subtypes. Conclusions: Chemotherapy use was lower among older patients with stage II/III breast cancer. Those with TN and HER2-positive BC had a lower BCSS than their younger counterparts. Chemotherapy may be beneficial in improving the OS in older patients with luminal and HER2-positive BCs. Treatment for older patients should be individualized, based on tumor-related factors, quality of life, and the patient's health status. Highlights: Chemotherapy use was low among patients aged ≥75 years. Triple-negative and HER2-positive subtypes had poor breast cancer-specific survival. Chemotherapy benefits in survival were seen in luminal and HER2-positive subtypes. The survival benefit of adjuvant chemotherapy differed by subtype.